a \({7^x} = 9\)

Show Solution
Okay, so we say above that if we had a logarithm in front the left side we could get the \(x\) out of the exponent. That’s easy enough to do. We’ll just put a logarithm in front of the left side. However, if we put a logarithm there we also must put a logarithm in front of the right side. This is commonly referred to as **taking the logarithm of both sides**.

We can use any logarithm that we’d like to so let’s try the natural logarithm.

\[\begin{align*}\ln {7^x} & = \ln 9\\ x\ln 7 & = \ln 9\end{align*}\]

Now, we need to solve for \(x\). This is easier than it looks. If we had \(7x = 9\) then we could all solve for \(x\) simply by dividing both sides by 7. It works in exactly the same manner here. Both ln7 and ln9 are just numbers. Admittedly, it would take a calculator to determine just what those numbers are, but they are numbers and so we can do the same thing here.

\[\begin{align*}\frac{{x\ln 7}}{{\ln 7}} & = \frac{{\ln 9}}{{\ln 7}}\\ x & = \frac{{\ln 9}}{{\ln 7}}\end{align*}\]

Now, that is technically the exact answer. However, in this case it’s usually best to get a decimal answer so let’s go one step further.

\[x = \frac{{\ln 9}}{{\ln 7}} = \frac{{2.19722458}}{{1.94591015}} = 1.12915007\]

Note that the answers to these are decimal answers more often than not.

Also, be careful here to not make the following mistake.

\[1.12915007 = \frac{{\ln 9}}{{\ln 7}} \ne \ln \left( {\frac{9}{7}} \right) = 0.2513144283\]

The two are clearly different numbers.

Finally, let’s also use the common logarithm to make sure that we get the same answer.

\[\begin{align*}\log {7^x} & = \log 9\\ x\log 7 & = \log 9\\ x & = \frac{{\log 9}}{{\log 7}} = \frac{{0.954242509}}{{0.845098040}} = 1.12915007\end{align*}\]

So, sure enough the same answer. We can use either logarithm, although there are times when it is more convenient to use one over the other.

b \({2^{4y + 1}} - {3^y} = 0\)

Show Solution
In this case we can’t just put a logarithm in front of both sides. There are two reasons for this. First on the right side we’ve got a zero and we know from the previous section that we can’t take the logarithm of zero. Next, in order to move the exponent down it has to be on the whole term inside the logarithm and that just won’t be the case with this equation in its present form.

So, the first step is to move on of the terms to the other side of the equal sign, then we will take the logarithm of both sides using the natural logarithm.

\[\begin{align*}{2^{4y + 1}} & = {3^y}\\ \ln {2^{4y + 1}} & = \ln {3^y}\\ \left( {4y + 1} \right)\ln 2 & = y\ln 3\end{align*}\]

Okay, this looks messy, but again, it’s really not that bad. Let’s look at the following equation first.

\[\begin{align*}2\left( {4y + 1} \right) & = 3y\\ 8y + 2 & = 3y\\ 5y & = - 2\\ y & = - \frac{2}{5}\end{align*}\]

We can all solve this equation and so that means that we can solve the one that we’ve got. Again, the ln2 and ln3 are just numbers and so the process is exactly the same. The answer will be messier than this equation, but the process is identical. Here is the work for this one.

\[\begin{align*}\left( {4y + 1} \right)\ln 2 & = y\ln 3\\ 4y\ln 2 + \ln 2 & = y\ln 3\\ 4y\ln 2 - y\ln 3 & = - \ln 2\\ y\left( {4\ln 2 - \ln 3} \right) & = - \ln 2\\ y & = - \frac{{\ln 2}}{{4\ln 2 - \ln 3}}\end{align*}\]

So, we get all the terms with \(y\) in them on one side and all the other terms on the other side. Once this is done we then factor out a \(y\) and divide by the coefficient. Again, we would prefer a decimal answer so let’s get that.

\[y = - \frac{{\ln 2}}{{4\ln 2 - \ln 3}} = - \frac{{0.693147181}}{{4\left( {0.693147181} \right) - 1.098612289}} = - 0.414072245\]

c \({{\bf{e}}^{t + 6}} = 2\)

Show Solution
Now, this one is a little easier than the previous one. Again, we’ll take the natural logarithm of both sides.

\[\ln {{\bf{e}}^{t + 6}} = \ln 2\]

Notice that we didn’t take the exponent out of this one. That is because we want to use the following property with this one.

\[\ln {{\bf{e}}^{f\left( x \right)}} = f\left( x \right)\]

We saw this in the previous section (in more general form) and by using this here we will make our life significantly easier. Using this property gives,

\[\begin{align*}t + 6 & = \ln 2\\ t & = \ln \left( 2 \right) - 6 = 0.69314718 - 6 = - 5.30685202\end{align*}\]

Notice the parenthesis around the 2 in the logarithm this time. They are there to make sure that we don’t make the following mistake.

\[ - 5.30685202 = \ln \left( 2 \right) - 6 \ne \ln \left( {2 - 6} \right) = \ln \left( { - 4} \right)\,\,{\mbox{can't be done}}\]

Be very careful with this mistake. It is easy to make when you aren’t paying attention to what you’re doing or are in a hurry.

d \({10^{5 - x}} = 8\)

Show Solution
The equation in this part is similar to the previous part except this time we’ve got a base of 10 and so recalling the fact that,

\[\log {10^{f\left( x \right)}} = f\left( x \right)\]

it makes more sense to use common logarithms this time around.

Here is the work for this equation.

\[\begin{align*}\log {10^{5 - x}} & = \log 8\\ 5 - x & = \log 8\\ 5 - \log 8 & = x\hspace{0.25in} \Rightarrow \hspace{0.25in}x = 5 - 0.903089987 = 4.096910013\end{align*}\]

This could have been done with natural logarithms but the work would have been messier.

e \(5{{\bf{e}}^{2z + 4}} - 8 = 0\)

Show Solution
With this final equation we’ve got a couple of issues. First, we’ll need to move the number over to the other side. In order to take the logarithm of both sides we need to have the exponential on one side by itself. Doing this gives,

\[5{{\bf{e}}^{2z + 4}} = 8\]

Next, we’ve got to get a coefficient of 1 on the exponential. We can only use the facts to simplify this if there isn’t a coefficient on the exponential. So, divide both sides by 5 to get,

\[{{\bf{e}}^{2z + 4}} = \frac{8}{5}\]

At this point we will take the logarithm of both sides using the natural logarithm since there is an **e** in the equation.

\[\begin{align*}\ln {{\bf{e}}^{2z + 4}} & = \ln \left( {\frac{8}{5}} \right)\\ 2z + 4 & = \ln \left( {\frac{8}{5}} \right)\\ 2z & = \ln \left( {\frac{8}{5}} \right) - 4\\ z & = \frac{1}{2}\left( {\ln \left( {\frac{8}{5}} \right) - 4} \right) = \frac{1}{2}\left( {0.470003629 - 4} \right) = - 1.76499819\end{align*}\]